Workforce Analytics: Need of the Modern Organisations - Srivastava, Nandini; Mohsin, Farhat (International Journal of Psychosocial Rehabilitation, 2020)
With the growth in industry and complexities in the corporate jobs, the volume of data has increased manyfold. Over the last 20 years, the companies have realized the importance of data and its interpretation in the effective management of business operations. Almost all organizations, in some way or other, are increasingly adopting analytics in the day-to-day activities of the organization. The scope of analytics is not confined to marketing and finance; rather, now the data available for HR to report has also increased and gained importance. Fields like talent acquisition, management, performance, compensation, etc., have started utilizing analytics for better results; however, most of the companies have yet to even realize the need for the use of analytics in the field of HR. According to a report published, most companies have not understood the value of their analytics investments, with only 12% of organizations currently using talent data to effectively influence business decisions and 70% of organizations expecting to increase the resources that they dedicate to talent analytics in recent times. The aim of this paper is to understand the rise of HR analytics over the last few years. This paper focuses on the role of stakeholders involved in HR, who have developed and positioned HR analytics as a necessary solution to existing and upcoming challenges